The International Monetary Fund's role in the euro-area crisis: Financial sector aspects - Nicolas Véron (Bruegel, 2016)
The International Monetary Fund (IMF) played a ground-breaking role in understanding the financial-sector dynamics of the euro-area crisis. It was the first public authority, and one of the first more generally, to acknowledge the role of the bank-sovereign vicious circle as the central driver of contagion in the euro area. It was the first public authority to articulate a clear vision of banking union as an essential policy response, building on its longstanding and pioneering support of banking policy integration in the European Union. At national level, the IMF's approach to the financial sector was appropriate and successful in Ireland and Spain, more limited in the Greek Stand-By Arrangement, and less compelling in Portugal where vulnerabilities remained when the country exited the programme. The IMF should further integrate financial-sector policy together with fiscal and macroeconomic issues at the core of its operations, and should devote particular effort to adapting its processes and methodologies to the new context of European banking union.
Keywords: 330